Hubungan Panjang Bobot dan Faktor Kondisi Ikan Tor (Tor spp.) di DAS Wampu Kabupaten Langkat, Provinsi Sumatera Utara, Indonesia - Isten Sweno Tamba; Desrita Desrita; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The objective of the present study was to evaluate the Length Weight Relationship (HPB) and Condition Factors of Tor Fish (Tor spp.) in Wampu River, Langkat River, North Sumatera Province, Indonesia. The sampling was This research used Post Facto Descriptive methos at two locations Bahorok and Berkail Rivers during three months July to September 2017. The research study show that the b value of Tor tambroides and Tor soro Fishes at Bahorok and Berkail river are among 0,297 until 0,328 or allometric negative with condition factor are among 0,01 until 1,00.Keywords: Tor spp., Lenght Weight Relationship, Condition Factor and Allometric negative